How GRAIL controls Treg function to maintain self-tolerance - Fathman, C. Garrison; Yip, Linda; Gómez-Martín, Diana; Yu, Mang; Seroogy, Christine M.; Hurt, Clarence R.; Lin, Jack T.; Jenks, Jennifer A.; Nadeau, Kari C.; Soares, Luis (Frontiers in Immunology, 2022)
Regulatory T cells (Tregs) normally maintain self-tolerance by recognizing “self”. When Tregs are defective, the immune system can attack and destroy one’s own tissues. Current therapies for autoimmunity rely on “treating” the destructive inflammation. Restoring defective endogenous immune regulation (self-tolerance) would represent a paradigm shift in the therapy of these diseases. One recent approach to restore self-tolerance is to use “low dose IL-2” as a therapy to increase circulating Treg numbers. However, studies to-date have failed to demonstrate significant clinical benefit. We hypothesize that the defect in self-tolerance is not due to insufficient Treg numbers, but may be due to defects in second messengers downstream of the IL-2R that normally control Treg function. Studies from our lab and others have demonstrated that GRAIL (a ubiquitin E3 ligase) is important in Treg function. GRAIL expression is diminished in Tregs from patients with autoimmune diseases and allergic asthma and is diminished in Tregs of autoimmune prone mice. In Tregs, GRAIL normally blocks cullin ring ligase activity, which inhibits IL-2R desensitization in Tregs and consequently promotes Treg function. As a result of this defect in GRAIL expression, the Tregs of patients with autoimmune diseases and allergic asthma degrade IL-2R-associated pJAK1 following activation with low dose IL-2, and thus cannot maintain the expression of pSTAT5 which controls the transcription of genes required for Treg function. Our data demonstrate that GRAIL acts a negative regulator of IL-2R desensitization by ubiquitinating a lysine on cullin5 that must be neddylated to allow cullin5 cullin ring ligase activity. We hypothesize that a neddylation inhibitor (NAEi) in combination with low dose IL-2 activation could substitute for GRAIL and restore Treg function. We generated a protein drug conjugate consisting of a NAEi bound to a fusion protein of IL-2, and showed that this drug was effective in blocking the onset or the progression of disease in several mouse models of autoimmunity (type 1 diabetes, systemic lupus erythematosus, and multiple sclerosis) and a mouse model of allergic asthma in the absence of detectable toxicity. This PDC strategy represents a novel targeted drug delivery system with maximal safety and efficacy.